Calcium isotope record of Phanerozoic oceans: Implications for chemical evolution of seawater and its causative mechanisms - Farkaš, Juraj; Eisenhauer, Anton; van Geldern, Robert; Munnecke, Axel; et al. (Geochimica Et Cosmochimica Acta, 2007)
A total of 280 brachiopods of Ordovician to Cretaceous age, complemented by published data from belemnites and planktonic foraminifera, are used to reconstruct the evolution of calcium isotope composition of seawater (δCa) over the Phanerozoic. The compiled δCa record shows a general increase from ∼1.3‰ (NIST SRM 915a) at the beginning of the Ordovician to ∼2‰ at present. Superimposed on this trend is a major long-term positive excursion from the Early Carboniferous to Early Permian as well as several short-term, mostly negative, oscillations. A numerical model of the global cycles of calcium, carbon, magnesium and strontium was used to estimate whether the recorded δCa variations can be explained by varying magnitudes of input and output fluxes of calcium to the oceans. The model uses the record of marine Sr/Sr ratios as proxy for seafloor spreading rates, a record of oceanic Mg/Ca ratios to estimate rates of dolomite formation, and reconstructed atmospheric CO, discharge and erosion rates to estimate continental weathering fluxes. The model results indicate that varying magnitudes of the calcium input and output fluxes cannot explain the observed δCa trends, suggesting that the isotope signatures of these fluxes must also have changed. As a possible mechanism we suggest variable isotope fractionation in the sedimentary output flux controlled by the dominant mineralogy in marine carbonate deposits, i.e. the oscillating 'calcite-aragonite seas'. The ultimate control of the calcium isotope budget of the Phanerozoic oceans appears to have been tectonic processes, specifically variable rates of oceanic crust production that modulated the hydrothermal calcium flux and the oceanic Mg/Ca ratio, which in turn controlled the dominant mineralogy of marine carbonates, hence the δCa. As to the causes of the short-term oscillations recorded in the secular δCa trend, we tentatively propose that these are related to variable rates of dolomite formation and/or to changing chemical composition of the riverine flux, in particular Ca / HCO and Ca / SO ratios, induced by variable proportions of silicate vs. carbonate weathering rates on the continents. © 2007 Elsevier Ltd. All rights reserve